Scene visualisation system development for noise modelling - Leow, Guan Wei (Nanyang Technological University, 2022)
Noise pollution is a cause for concern, especially since it has detrimental health effects. Due to Singapore’s limited geographical size and rising population density, gas stations, roads, and even expressways are built close to residential neighbourhoods. Noise pollution in such areas is a significant problem, as a result of frequent traffic on these routes, especially during rush hours. The purpose of this project is to create a pipeline from a scene simulation to modelling noise propagation. This project aims to develop a scene modelling platform that will help bridge the gap between scene and noise modelling. It also aims to investigate different noise barriers and their effectiveness against vehicular noise pollution. There are 3 main components of this paper: 1. Data preprocessing and exploratory analysis of the scene data. 2. Design methodology and implementation of the scene modelling platform. 3. Noise propagation experiments and evaluations. In component 1, retrieval of scene data such as trees and buildings is explained. Data from trees were crawled from TreesSG, while data from buildings were a combination of HDB as well as OSM buildings data. These datasets were then analysed, and preprocessed to suit the scene modelling platform, as well as for noise modelling. In component 2, the design methodology is explained, with figures such as a system architecture diagram, a use case diagram, and a dialog map. There are also descriptions of the functional and non-functional requirements, as well as figures of the system’s interface. The platform is developed such that the scene data from component 1 is inserted and visualised, enabling exportation of data to a format suitable for component 3. In component 3, several experiments that were carried out in a controlled environment using NoiseModelling tool and are discussed and analysed. These experiments examine how different noise barriers, tree shapes and tree properties 3 affect noise propagation to buildings. There is also an evaluation of noise propagation using real-world data. These experiments and evaluations were carried out to determine the most practical and efficient methods for mitigating vehicular noise pollution in residential areas.